Conceptual analysis: What signals might plant canopies send via stemflow? - Mabrouk, Adam I.; Gordon, D. Alex; Gotsch, Sybil G.; Van Stan, John T. (Frontiers in Water, 2022)
As watersheds are complex systems that are difficult to directly study, the streams that drain them are often sampled to search for watershed “signals.” These signals include the presence and/or abundance of isotopes, types of sediment, organisms (including pathogens), chemical compounds associated with ephemeral biogeochemical processes or anthropogenic impacts, and so on. Just like watersheds can send signals via the streams that drain from them, we present a conceptual analysis that suggests plant canopies (equally complex and hard-to-study systems) may send similar signals via the precipitation that drains down their stems (stemflow). For large, tall, hard-to-access tree canopies, this portion of precipitation may be modest, often <2%; however, stemflow waters, like stream waters, scour a large drainage network which may allow stemflow to pick up various signals from various processes within and surrounding canopies. This paper discusses some of the signals that the canopy environment may impart to stemflow and their relevance to our understanding of vegetated ecosystems. Being a conceptual analysis, some examples have been observed; most are hypothetical. These include signals from on-canopy biogeochemical processes, seasonal epi-faunal activities, pathogenic impacts, and the physiological activities of the canopy itself. Given stemflow's currently limited empirical hydrological, ecological and biogeochemical relevance to date (mostly due to its modest fraction in most forest water cycles), future work on the possible “signals in stemflow” may also motivate more natural scientists and, perhaps some applied researchers, to rigorously monitor this oft-ignored water flux.